Developing Fictional Characters in Picture Stories: A Lesson on Minangkabau Customs for the Alpha Generation - Fitri, Diana; Sahrul, Sahrul (Gorga : Jurnal Seni Rupa, 2025)
Cultivating respect and appreciation among others is paramount in interpersonal interactions, thereby establishing an ethical foundation for effective communication. The Alpha generation, known for its challenging social nature, can benefit from learning Minangkabau customs and etiquette as a means of developing effective communication and social skills. This design aims to educate children about Minangkabau cultural norms through the design of character designs tailored for the Alpha generation, specifically children aged 7-10 years, who are in the third grade of elementary school. The design is presented in a fictional form as a communication medium. The research methodology employed includes the glass box method and the 5w + 1H analysis method, which are recommended to enhance the design’s effectiveness. Data was gathered through observations of children’s interactions and their display of polite behavior towards both peers and older individuals. These observations served as the inspiration for this design. The resulting design presents a learning media platform that features visually appealing character designs. The ultimate goal of this design is to create a character story that embodies Minangkabau manners, serving as a fictional narrative for Alpha generation children. This character design will later be used to represent the broader identity of Minangkabau, which will be further developed into a picture storybook for the next stage of the project.